Comparison of Hanafi and Mutakallimin Methods in Islamic Jurisprudence Formulation - Ulil Albab Al aulia Alpaten; Rustam Dahar Karnadi Apollo Harahap; Akbar Fatih Zulfikhar (Universitas Islam Negeri Sumatera Utara, 2025)
The study examines the effectiveness of the Hanafi method in establishing jurisprudence rules and compares it with the Mutakallimin method. Through a qualitative descriptive approach, utilizing primary data from Hanafi fiqh and Mutakallimin books along with secondary data from scholarly journals and online articles, the research elucidates the nuances of both methodologies. The Hanafi method, rooted in the teachings of Imam Abu Hanifah and his companions, prioritizes practical aspects and real-world experience in jurisprudence formulation. Employing an inductive approach, it offers flexibility and rational interpretation, ensuring relevance in evolving contexts. In contrast, the Mutakallimin method focuses on establishing rules of usuliyah without considering fiqh branches, emphasizing reasoning but criticized for its rigidity and lack of practical examples. The findings suggest that the Hanafi method, with its clarity, comprehensiveness, and flexibility, is more effective in jurisprudential development. It incorporates principles derived from earlier imams, facilitating understanding and application. Conversely, the Mutakallimin method, while valuing reasoning, faces challenges in application due to its detachment from fiqh branches. Thus, the Hanafi method emerges as a more practical and relevant approach, contributing significantly to the evolution and application of Islamic law in contemporary contexts